Lagos State, Nigeria : PIM Investment in Infrastucture for a Modern Megacity - Treichel, Volker; Ebenerze Oyewol, Olubgenga (World Bank, Washington, DC, 2014)
Lagos State is one of the fastest growing metropolises in the world. Under the Governor s Ten Point Agenda (TPA), Lagos State has made substantial progress in creating the basis for sustained growth by improving infrastructure and strengthening the business environment. Improved public investment management (PIM) has been at crucial element of these reform efforts. This paper reviews the reform efforts of the Lagos State Government in strengthening the planning and execution of expenditures, and rates the quality of PIM. The study make the case that the overall practices in PIM in Lagos State are still weak, but have made encouraging leaps toward improvement, including passage by the legislature of several important bills, such as the Lagos State Procurement Bill 2009, Lagos State Tenancy Bill 2009, Lagos State Public Finance Management Bill 2010, and the Criminal Law of Lagos State Bill 2010. However, a major issue that will continue to impose hurdles and pressure on the ability of the State Government to effectively plan, implement, and monitor public investment in a systematic and comprehensive manner is the huge relative size of the Lagos State economy !and the ever increasing population of the State, which threatens!to!outpace!progress!in!developing!relevant!institutional!capacity.